2009
DOI: 10.1152/ajpcell.00650.2008
|View full text |Cite
|
Sign up to set email alerts
|

Determination of apparent calcium affinity for endogenously expressed human sarco(endo)plasmic reticulum calcium-ATPase isoform SERCA3

Abstract: Chandrasekera PC, Kargacin ME, Deans JP, Lytton J. Determination of apparent calcium affinity for endogenously expressed human sarco(endo)plasmic reticulum calcium-ATPase isoform SERCA3. Am J Physiol Cell Physiol 296: C1105-C1114, 2009. First published February 18, 2009 doi:10.1152/ajpcell.00650.2008.-The sarco(endo)plasmic reticulum Ca 2ϩ -ATPases (SERCAs) play a crucial role in regulating free cytosolic Ca 2ϩ concentration in diverse cell types. It has been shown that recombinant SERCA3, when measured in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 52 publications
2
40
0
Order By: Relevance
“…The quantity of the transported Ca 2+ ions depends on c cyt levels. We assume a linear relationship, because the ER influx is also composed of different SERCA pumps with different K d values [40]. Nevertheless, our model can also work when EFF or/and SERCA fluxes were simulated with the conventional Hill equations.…”
Section: Building Up the Modelmentioning
confidence: 99%
“…The quantity of the transported Ca 2+ ions depends on c cyt levels. We assume a linear relationship, because the ER influx is also composed of different SERCA pumps with different K d values [40]. Nevertheless, our model can also work when EFF or/and SERCA fluxes were simulated with the conventional Hill equations.…”
Section: Building Up the Modelmentioning
confidence: 99%
“…Transport activity is stimulated by calcium in a concentration-dependent manner [44,45,46]. When the calcium concentration dependency of calcium transport by various SERCA isoforms was compared, it has been shown that the apparent calcium affinity (K Ca 2+ , as defined by the calcium concentration that leads to half-maximal induction of transport) of all SERCA3 isoforms is weaker (approximately 1.2 μM) than that of other isoforms, and in particular of SERCA2b (0.2 μM) [35,47,48,49,50,51]. Based on this observation SERCA2b is thought to be a more “stringent” calcium pump than SERCA3: whereas SERCA2b-dependent calcium sequestration is fully active already above the 0.2 μM cytosolic calcium concentration range, fully active calcium sequestration by SERCA3 would be observed only above 1.2 μM calcium, and SERCA3 would pump calcium very weakly at around 0.2 μM [35,37,39].…”
Section: The Serca Multigene Family Co-expression Of Serca2 and Smentioning
confidence: 99%
“…Normal heart function would require both ER and SR compartments. While further work is required to understand the mechanisms responsible for the low affinity of the SERCA2c and SERCA3 isoforms [15,19,26,27,[82][83][84], the coexpression of these types of SERCA isoform with the SERCA2a and -2b types can be required for normal heart function. Some data may indicate that there needs to be a balance between SERCA isoforms in the human heart, in terms of their affinities towards Ca 2+ for normal heart function.…”
Section: Compensatory Mechanisms and Abnormal Sr/er Function In Heartmentioning
confidence: 99%